IMPLEMENTASI LAYANAN BIMBINGAN KARIR BAGI ANAK TUNAWICARA DI SMPLB YPAC PALEMBANG [IMPLEMENTATION OF CAREER GUIDANCE SERVICE FOR SPEECH IMPAIRED CHILDREN IN SMPLB YPAC PALEMBANG] - Syeilla Amrina Rosyada; Aziz Muslim (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
This study aims to determine the concept of career development for a speech impaired, as well as to understand the concept of implementation of development and strategies for the development of career guidance for a speech impaired children at SMPLB YPAC Palembang. This study uses qualitative research using data analysis techniques with Miles and Huberman models, data collection techniques through primary data, and secondary data through observation, in-depth interviews, and documentation. The findings of this study are a career guidance that has been programmed in a guidance and counseling services. But in its implementation it is not optimal, because there is several obstacles both in terms of learning and needs, learning barriers here are not optimal planning and a preparation of a career guidance programs. Career guidance services are a principle for children with special needs or children with disabilities where each process is the same as a career guidance for students in regular schools,but there is slight differences in the stages of implementation, services, development strategies and the results of a career guidance programs obtained for children with special needs or a speech impaired children.